An Empirical Analysis of School Students’ Continuance Intention to Use Mobile Learning - Singh, Yashdeep; Suri, Pradeep Kumar (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
School students are increasingly using mobile applications to enhance their learning. The adoption of mobile learning (m-learning) apps by students was accelerated by nearly two years of partial or complete school closures due to the Coronavirus disease (COVID-19) pandemic. The students adopted and experienced m-learning. The intention to continue using a technology is determined by several factors. This study used the factors adapted from the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) to examine a school student’s continuance intention (CI) to use m-learning. Structural equation modelling analysis was used to investigate the impact of social influence (SI), facilitating conditions (FC), perceived usefulness (PU), and perceived enjoyment (PE) on CI. The study collected data from 366 students attending public and private schools in the National Capital Territory (NCT) of Delhi, India, using a paper-based survey. The results revealed that SI and PE predicted CI. Interestingly, PU had an insignificant direct but significant indirect effect on CI. In addition, implications for researchers, m-learning app managers, and developers are discussed.